The art of discomfort: engaging in dialogue on war. Issue 1 (2nd January 2019) - Eichler, Maya; Wiebe, Jessica Lynn
ABSTRACT: Dialogue on war is difficult and uncomfortable, for both political and personal reasons. In this article, Maya Eichler, a feminist scholar of militaries and military conflict, and Jessica L. Wiebe, a female veteran artist, describe their experiences of co-writing and co-performing "The Weight We Share." Drawing inspiration from Sarah Bulmer and David Jackson's piece "You do not live in my skin", they share these reflections on their collaborative work to illustrate how art has helped them to sit with the discomfort of engaging in conversations that challenge deeply-held beliefs and emotions about the military and war.